O eterno, o humano e a liberdade: a afirmação da ideia de liberdade pela via do livre-arbítrio no pensamento de Santo Agostinho - Guilherme dos Reis Soares (2022)
In the trajectory of the West, the existence of an idea of freedom that supported the emergence of it as a legal construction can be noted, as a fact that at different times, the theme emerged, even without connection with a legally designated right. This idea is the result of a long process of conception, conceptualization and polishing, point in which medieval Christian thought has its importance. Augustine of Hippo was one of the authors who most profoundly influenced Christian thought in the Middle Ages, and in his search for truth, he endeavored to amalgamate elements of the philosophical tradition of antiquity with the foundations of the Christian religion, that emerged in Late Antiquity. The Bishop of Hippo was born and lived in an environment of change, witnessing the decline and end of the Western Roman Empire, as well as the Barbarian invasions. Like his context, his formation and conversion process are marked by the relationship between paganism and Christianity, which provided him with a vast intellectual wealth and means to move well in both environments, which was reflected in his extensive philosophical production. Among the countless possible points, the present study seeks to understand the idea of freedom that emerges from the thought of Saint Augustine. Because it is notably a theoretical research, its main tool was the bibliographic review, in an attempt to raise influences and contributions from other authors to the Hiponense thought. Methodologically, the study adheres to the macro philosophical perspective, envisioning the possibility of greater interdisciplinarity in the legalphilosophical study, permeating Law, Philosophy, History and Theology. At the same time, an expanded view of Saint Augustine's own philosophical construction was sought, understanding it in the context of Late Antiquity, with its roots deeply cast in Platonism and Neoplatonism. This allows us to glimpse its relationship with the previous philosophical tradition, as well as its contribution to Western thought. Structured in three chapters, the study initially sought to understand the theorization of the Eternal, through the influences of Manichaeism and Catholic Christianity, where Augustine finds God as a spiritual totality that inhabits creation. In his complex relationships with God, the human element was delimited, at which point Augustine describes the role attributed to sensitivity and rationality, as well as the importance of divine enlightenment. Finally, emerging from the relationship between the Eternal and the Human elements, the idea of freedom emerges. Augustine advances on the question of the origin of evil to consolidates the role of free will, distancing himself from the tradition that preceded him, and opening a new horizon of possibilities for men, who no longer saw themself chained to destiny. Through free will, Augustine theorizes an idea of freedom that summarizes men's path back to the divine, since, taking advantage of his rationality, and enlightened by God, men must understand the order of the world, hierarchize what it must be used and enjoyed, and direct its will to what is the true end itself, namely, beatitude, thus coming to the contemplation and enjoyment of God.